Highly Hydrophobic ZIF‐8/Carbon Nitride Foam with Hierarchical Porosity for Oil Capture and Chemical Fixation of CO2. (11th April 2017) - Kim, Daeok; Kim, Dae Woo; Buyukcakir, Onur; Kim, Min‐Kyeong; Polychronopoulou, Kyriaki; Coskun, Ali
Abstract : The introduction of hierarchical porosity into metal‐organic frameworks (MOFs) has been of considerable interest in gas separation and heterogeneous catalysis due to the efficient mass transfer kinetics through meso/macropores. Here, a facile, scalable approach is reported for the preparation of carbon nitride (CN) foams as structural templates with micrometer‐sized pores and high nitrogen content of 25.6 wt% by the fast carbonization of low‐cost melamine foam. The nitrogen functionalities of CN foam facilitate chemical anchoring and growth of ZIF‐8 (zeolitic imidazolate frameworks) crystals, which leads to the development of hierarchical porosity. The growth of ZIF‐8 crystals also renders CN foam, which is hydrophilic in nature, highly hydrophobic exhibiting 135° of water contact angle due to the enhanced surface roughness, thus creating a natural shield for the MOF crystals against water. The introduction of ZIF‐8 crystals onto the CN foam enables selective absorption of oils up to 58 wt% from water/oil mixtures and also facilitates the highly efficient conversion of CO2 to chloropropene carbonate in a quantitative yield with excellent product selectivity. Importantly, this present approach could be extended to the vast number of MOF structures, including the ones suffering from water instability, for the preparation of highly functional materials for various applications. Abstract : A facile, scalable carbonization strategy is introduced for the preparation of carbon nitride foams with high nitrogen contents and micrometer‐sized pores as a structural template for the growth of ZIF‐8 crystals. This renders the resulting frameworks highly hydrophobic such that they can be used to clean up oil spills from water and are catalytically active for CO2 conversion.